Porous organic polymer (POP) nanosheets: an efficient photo-catalyst for visible-light assisted CO2 reduction. Issue 7 (2nd March 2022) - Das, Surya; Chowdhury, Ipsita Hazra; Chakraborty, Adwitiya; Naskar, Milan Kanti; Sarkar, Mitali; Manirul Islam, S. K.
Abstract : We have designed a nano-sheet-like porous organic polymer (POP) constructed via a schematic hydrothermal process and characterized it using PXRD, N2 adsorption–desorption studies, UV-vis, XPS and microscopic analyses (TEM and FESEM). Abstract : We have designed a nano-sheet-like porous organic polymer (POP) constructed via a schematic hydrothermal process and characterized it using PXRD, N2 adsorption–desorption studies, UV-vis, XPS and microscopic analyses (TEM and FESEM). The synthesized POP can perform as a dynamic photo-catalyst for the production of formic acid and formaldehyde. This pure polymeric porous photo-catalytic system demonstrates exceptionally good catalytic performances for the generation of formic acid (major product) and formaldehyde (minor product) with TON values of 355 and 47, respectively, under visible light irradiation. The as-synthesized catalyst also exhibited excellent yield for the synthesis of both products HCOOH (TON: 338) and HCHO (TON: 10) even under sunlight irradiation. The recyclability of the photo-catalyst is also confirmed for five reaction cycles and the POP material showed excellent recycling capability without any visible catalyst degradation.